Diffuse Axonal Damage in Head Traumas the Role of B-App in Diagnosis - Karayel, Ferah; Sav, Aydın (The Bulletin of Legal Medicine, 2008)
One of the most significant reasons of death or extended neurological deficits in the persons suffering head trauma of differing levels is the diffuse axonal damage (DAD). In autopsy cases, DAD diagnosis could be possible on the samples to be taken from suitable parts of the brain, by microscopic examination of the sections stained with Hematoxyline Eosin. But, in the posttraumatic period, in the cases who lived for a very short time, since the morphological findings of the damage has not fully formed, it is difficult to diagnose DAD. ß-APP plays an important role in such cases for diagnosing DAD. Its most evident superiorities are its reflection of the loss which took place while alive, it marks only damaged axons and it is not influenced by the postmortem interval. The aim of this study is to review the morphological findings associated with mechanism of development of DAD, to stress the importance and role of ß-APP in the evaluation of the cases with a history of head trauma.Key words: Trauma, brain, diffuse axonal damage, ß-APP
Keywords: trauma; brain; diffuse axonal damage; ß-app